Influence of plastic deformation on electrochemical properties of X5CrNi18-10 steel - Rejmer, Wojciech (Technical Sciences, 2020)
The purpose of the work was to determine the effect of plastic deformation on the electrochemical properties of X5CrNi18-10 steel. The tested material belongs to the group of stainless steels with low carbon content and is used in many industries due to high corrosion resistance. In most applications of the tested material, it is formed into complicated shapes and exposed to aggressive environments. An example can be applications in medicine (implants) as well as in civil engineering and nuclear energy The literature on the subject shows a different impact of deformation on anti-corrosion properties. Samples with 5 different deformations were obtained. Electrochemical direct electrical current and alternating electrical current tests were performed for the obtained materials. The tests were carried out in a 1 molar sodium chloride solution. Studies have shown an increase in corrosion resistance of samples with increasing strain in the tested strain ranges.